2019
DOI: 10.5539/gjhs.v11n13p135
|View full text |Cite
|
Sign up to set email alerts
|

What Do Patients Expect of Health Care Providers? Patient Perceptions and Expectations of Professionalism in Optometry Practice in KwaZulu-Natal, South Africa

Abstract: BACKGROUND: Professionalism, which includes factors such as attire, hygiene, communication skills, compassion and empathy; has not been previously investigated in the discipline of Optometry and yet is known to be influential in building patient-practitioner relationships. METHODS: This study was conducted at public and private eye care facilities in KwaZulu-Natal (KZN), South Africa. Convenience sampling was used to select 600 participants and data collected with a self-administered questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Poor eye contact and poor listening were the 2 factors most prominent in these consultations. Gorawara-Bhat and Cook 44 connected eye contact and listening as 2 crucial components of patient-centeredness. Eye contact is often sensitive in Africa, as some people claim that in certain cultures, adults do not to tolerate younger people making direct eye contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor eye contact and poor listening were the 2 factors most prominent in these consultations. Gorawara-Bhat and Cook 44 connected eye contact and listening as 2 crucial components of patient-centeredness. Eye contact is often sensitive in Africa, as some people claim that in certain cultures, adults do not to tolerate younger people making direct eye contact.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a study conducted in rural KwaZulu Natal, in an optometry setting, found that an introduction between the professional and patient and maintaining eye contact ensured that 75.6% of the participants considered the professional as more reliable. 44 Doctor 9 in Consultation 2 demonstrated good eye contact with the patient during the entire The components of the consultation namely medical history, examination, and discussion of care and treatment − all of which are grounded in evidence-based criteria or standards.…”
Section: Interruptionsmentioning
confidence: 99%